Aggressiveness tax in indonesia - Dewi, Sofia Prima; Cynthia, Cynthia (Jurnal Akuntansi, 2018)
The purpose of this study was to obtain empirical evidence about the influence of liquidity, corporate social responsibility, earnings management, and firm size against tax aggressiveness on manufacturing companies listed consistently in the Indonesia Stock Exchange during the year 2013-2015. This study used a sample of sixty-four manufacturing companies. This study uses a software program Eviews for data processing. These results indicate that liquidity has an influence on tax aggressiveness, while corporate social responsibility, earnings management, and firm size have no influence on tax aggressiveness.